The Effect of Sales Accounting Information System and Cash Receipt on The Implementation of Internal Control - Vicky Dzaky Cahaya Putra; Sofia Windiarti (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
The sales Accounting Information System and Cash Receipts is one of the sub-systems of accounting information that explains how the procedures should be in carrying out sales activities and Cash Receipts from sales so that manipulation of sales and Cash Receipts can be avoided. Effective of Internal Control using the Committee of Sponsoring Organizations of the Treadway Commission (COSO) is required to coordinate and supervise the course of company activities. This is intended to avoid things that can cause company losses such as fraud, waste, and theft from inside and outside the company in assessing the company as well as to evaluate and take corrective action in anticipating company weaknesses. This type of research is used based on the research objectives is associative, namely research that examines the relationship of three variables, namely the relationship between the variables of Sales Accounting Information System and Cash Receipts on Internal Control. The data source used in this study, namely primary data. Primary data was obtained through a questionnaire technique. The population chosen was employees of the sales and finance division of the Lintasarta Branch Office of West Java Province with a sample of 58 employees who were processed using the Slovin formula. keywords: Sales Accounting Information System, Cash Receipts, Internal Control